Optimalisasi Kotoran Sapi sebagai Pupuk Organik Ramah Lingkungan di Desa Sunggam Tonga - Farhan Siregar; Pratama Hidayah Nuddin Tanjung; Iman Fahri; Marzuq Affandi; Zulfahmi (Bengkulu Institute, 2025)
The accumulation of untreated livestock waste and the excessive reliance on inorganic fertilizers are significant agricultural issues in Sunggam Tonga Village. This community service program aimed to empower farmers by transferring technology to optimize cow manure into environmentally friendly organic fertilizer. The method employed was a participatory approach involving field observations, interviews, socialization, and a technical demonstration of the fermentation process. The production process utilized cow manure mixed with rice husks and enriched with rice washing water, using Effective Microorganisms 4 (EM4) as a bioactivator to accelerate decomposition. The activity resulted in the successful production of mature solid organic fertilizer within 14 days, characterized by a crumbly texture, dark color, and the absence of a foul odor. The program effectively increased community knowledge regarding waste management and provided a practical skill set for producing nutrient-rich compost. It is concluded that this appropriate technology offers a sustainable solution for mitigating environmental pollution caused by livestock waste while reducing farming production costs.